2021
DOI: 10.1136/bjophthalmol-2020-318529
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of intravitreal topotecan dose levels, toxicity and efficacy for retinoblastoma vitreous seeds: a preclinical and clinical study

Abstract: BackgroundCurrent melphalan-based intravitreal regimens for retinoblastoma (RB) vitreous seeds cause retinal toxicity. We assessed the efficacy and toxicity of topotecan monotherapy compared with melphalan in our rabbit model and patient cohort.MethodsRabbit experiments: empiric pharmacokinetics were determined following topotecan injection. For topotecan (15 μg or 30 µg), melphalan (12.5 µg) or saline, toxicity was evaluated by serial electroretinography (ERG) and histopathology, and efficacy against vitreous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 39 publications
1
16
0
Order By: Relevance
“…Second, our previous work with other drugs had demonstrated that intravitreal and intra-arterial injections of various other drugs leads to high but transient vitreous concentrations, with relatively rapid efflux. 24 , 25 Thus, following intravitreal injection, the vitreous seeds would only be exposed to the initial high concentration very briefly. We therefore determined the vitreous half-life to ensure that the dose calculated for the initial injection would allow a concentration (on the opposite side of the vitreous) above the IC 90 for a length of time equivalent to at least 5 half-lives.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Second, our previous work with other drugs had demonstrated that intravitreal and intra-arterial injections of various other drugs leads to high but transient vitreous concentrations, with relatively rapid efflux. 24 , 25 Thus, following intravitreal injection, the vitreous seeds would only be exposed to the initial high concentration very briefly. We therefore determined the vitreous half-life to ensure that the dose calculated for the initial injection would allow a concentration (on the opposite side of the vitreous) above the IC 90 for a length of time equivalent to at least 5 half-lives.…”
Section: Discussionmentioning
confidence: 99%
“…Human WERI-Rb1 retinoblastoma cells were grown in RPMI with 10% fetal bovine serum under normal growth conditions, as reported previously. 24 , 33 Five thousand cells were plated in 96-well plates and exposed to belinostat at various concentrations for 4 hours (equivalent to 5 half-lives as determined through the above-described pharmacokinetic experiments). The belinostat-containing media were then removed and replaced with fresh media.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations